2019
DOI: 10.1053/j.gastro.2018.12.006
|View full text |Cite
|
Sign up to set email alerts
|

New and Recurrent Colorectal Cancers After Resection: a Systematic Review and Meta-analysis of Endoscopic Surveillance Studies

Abstract: Background & Aims: Outcomes of endoscopic surveillance following surgery for colorectal cancer (CRC) vary with the incidence and timing of CRC detection, at anastomoses or nonanastomoses in the colorectum. We performed a systematic review and meta-analysis to evaluate the incidence of CRCs identified during surveillance colonoscopies of patients who have already undergone surgery for this cancer. Methods: We searched PubMed, EMBASE, SCOPUS, and the Cochrane Central Register of Clinical Trials through January 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 38 publications
3
38
0
Order By: Relevance
“…Three studies presented evidence per age group relative to the younger age group. Martinez et al 12 reported statistically significant increased risks for AN across three age groups (61–71; 80+years) compared with the younger age group (50–59 years), with incidence of AA at first surveillance as 12.2%, 14.5%, and 17.7%, respectively. Furthermore, Martinez et al also presented evidence on the younger than 40 age group, and the 40–49 age group relative to the 50–59 age group.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Three studies presented evidence per age group relative to the younger age group. Martinez et al 12 reported statistically significant increased risks for AN across three age groups (61–71; 80+years) compared with the younger age group (50–59 years), with incidence of AA at first surveillance as 12.2%, 14.5%, and 17.7%, respectively. Furthermore, Martinez et al also presented evidence on the younger than 40 age group, and the 40–49 age group relative to the 50–59 age group.…”
Section: Resultsmentioning
confidence: 98%
“…The presence of synchronous CRC was the only significant risk factor for developing metachronous CRC (RR 13.9, 95% CI 4.7 to 41.0). However, a recent systematic review and meta-analysis shows that the absolute risk is substantially lower than 1%, ranging between 0.63% and 0.74% in the first 3 years of follow-up, further dropping to <0.5% after 36 months 66…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a large retrospective cohort study from the UK evaluating the effectiveness of post-polypectomy colonoscopy surveillance on incident colorectal cancer, Cross et al reported that, compared with the general population, CRC incidence without surveillance was similar among low-risk and intermediate-risk groups, but significantly higher in the high-risk group. However, a possible exception is the need for early colonoscopy surveillance following complex polyp resection (for example, endoscopic mucosal resection or endoscopic submucosal dissection) or following endoscopic management of early gastric cancer because these patients have been shown to be at high-risk for residual or recurrent disease 9,10 . Delays for endoscopic surveillance are now common owing to endoscopy units temporarily suspending such procedures, a lack of endoscopy personnel to perform these procedures as many have been assigned to other medical wards to care for patients with COVID-19 or are sick or isolating themselves, or because patients decide to stay away from hospitals.…”
mentioning
confidence: 99%
“…5 These mechanisms apply both to cancers occurring after a clear colonoscopy, and to metachronous cancers occurring after a colorectal cancer is resected, which occurs after up to 3% of surgical resections. 6,7 In this issue of Gastroenterology, Backes et al in a proof-of-principle study suggest a fifth mechanism for development of colorectal cancer after colonoscopy: iatrogenic mechanical tumor seeding via the biopsy channel of the colonoscope (Figure 1). 8 Causality of seeding after biopsy is difficult to prove.…”
mentioning
confidence: 99%